Secular Possession: Cinematic Iconography of Addiction - Rantala, Varpu (fi=Turun yliopisto|en=University of Turku|, 2016)
Addiction, and the experience of being addicted, is notoriously difficult to describe verbally and explain rationally. Would multifaceted and multisensory cinematic images work better in making addiction understandable? This study enquires how cinematic expression can render visible the experience of being addicted which is invisible as such. The basic data consists of circa 50 mainly North American and European fiction films from the early 1900s to the early 2000s that deal with addictive disorders as defined in the psychiatric DSM-V classification (substance dependence- and gambling disorders). The study develops an approach for analyzing and interpreting a large volume of digital film data: digital cinematic iconography is a framework to study the multifaceted cinematic images by processing and viewing them in the “digital image-laboratory” of the computer. Images are cut and classified by editing software and algorithmic sorting. The approach draws on early 1900s German art historian Aby Waburg’s image research and media archaeology, that are connected to film studies inspired by the phenomenology of the body and Gilles Deleuze’s film-philosophy. The first main chapter, “Montage”, analyses montage, gestural and postural images, and colors in addiction films. The second main chapter, “Thingness”, focuses on the close-ups of material objects and faces, and their relation to the theme of spirituality in cinema and art history, The study argues that the cinema engages the spectator to "feel" what addiction is through everyday experience and art historical imagery. There is a particular, historically transmitted cinematic iconography of addiction that is profane, material, thing-centered, abject, and repetitive. The experience of being addicted is visualized through montages of images characterized by dark and earthy colors, horizontal compositions and downward- directed movements. This is very profane and secular imagery that, however, circulates image-historical traces of Christian iconography, such as that of being in the grip of an unknown power.

Addiktion kokemusmaailmaa on vaikeaa kuvata sanallisesti ja selittää rationaalisesti. Pystyykö elokuvan moniulotteinen kuvallinen ilmaisu tähän paremmin? Väitöstutkimus kysyy, kuinka elokuvallisen ilmaisun tekniikoita on käytetty kuvaamaan addiktion kokemusmaailmaa, joka ei ole suoraan nähtävissä. Pääasiallinen aineisto muodostuu noin 50:stä yhdysvaltalaisesta ja eurooppalaisesta fiktioelokuvasta 1900-luvun alusta 2000-luvun alkuun. Elokuvat käsittelevät psykiatrisessa DSM-V–luokituksessa määriteltyjä riippuvuusongelmia (huumausaine-, alkoholi- ja peliriippuvuutta). Tutkimus kehittää elokuvan digitaaliseksi ikonografiaksi nimetyn menetelmän, joka mahdollistaa suuren kuvadatan käsittelyn ja tulkinnan elokuvan estetiikan näkökulmasta. Tutkimuksessa kerätään, leikataan ja luokitellaan addiktion kuvaamisen kuvatyyppejä editointiohjelmistojen ja algoritmisen analyysin keinoin. Tällöin kuvien leikkaaminen ja uudelleenyhdistely, montaasi, on myös tutkimusmenetelmä. Lähestymistapa rakentuu 1900-luvun alussa vaikuttaneen saksalaisen taidehistorioisijan Aby Warburgin kuvatutkimuksen kautta yhdistämällä media-arkeologiaa ja ruumiinfenomenologista, Gilles Deleuzen elokuvafilosofiasta vaikutteita saanutta elokuvatutkimusta. Tutkimuksessa on kaksi päälukua, joista ensimmäinen käsittelee montaasia ja toinen esineisyyttä. Tutkimus esittää, että addiktion elokuvallinen ikonografia perustuu tuntemattoman voiman vallassa olemiseen, joka rakentuu montaasin ja tiettyjen, usein toistuvien kuvatyyppien kautta. Addiktion elokuvallinen ikonografia on profaania, materiaalista, esinekeskeistä ja abjektista (eli likaan ja moraaliseseti tuomittavaan liittyvää inhoa herättävää). Vaikeasti sanallistettavaa kokemusta kuvaavat tummat ja maanläheiset värit, vaakasommitelmat ja alaspäin suuntautuvat liikkeet. Sekulaari ja maanläheinen kuvasto kierrättää myös kristillisestä ikonografiasta tuttuja asetelmia. Tutkimuksen perusteella elokuvallinen ilmaisu pyrkii tekemään addiktion kokemusmaailmaa ymmärrettäväksi ammentamalla arkisesta kokemusmaailmasta ja voimakkaiden tunnekokemusten kuvaamisen historiasta.